Prevalence of mucocutaneous manifestations in human immunodeficiency infection - learning from a rural centre in Tamilnadu, India - Vedhanayagam, Mohankumar; Rajagopalan, Rajesh (International Journal of Research in Medical Sciences, 2017)
Background: Ever since its recognition in 1981, HIV continues to ravage all the continents of the world. HIV infection produces a panorama of mucocutaneous manifestations ranging from the macular rash seen in acute ‘sero conversion’ syndrome to extensive end-stage Kaposi’s sarcoma. Skin disease may be the first presenting feature of the disease and it raises the suspicion to screen for HIV infection. Disease progression may result in significant morbidity. Methods: This study was undertaken in 116 People living with HIV, who attended the well health clinic in Department of Skin and STD, IRT Perundurai Medical College, Erode, in rural Tamilnadu, from 15th June 2005 to 14th August 2005. The study patients were interviewed after pre and post-test counselling. All the patients underwent a complete physical and genital examination with keen clinical analysis for the mucocutaneous manifestations of HIV infection. Results: 96% of HIV positives in our study had mucocutaneous manifestations. Commonest disease observed was oral candidiasis n=63 (56.25%). Dermatophytosis n=46 (41.07%) was the second most common infection followed by papular and follicular eruptions in HIV (n=34, 30.3%). Conclusions: Respiratory system illnesses were the commonest presenting opportunistic illnesses followed by the gastrointestinal tract.